Smokestacks in the Hills: Rural Industrial Workers in West Virginia - MacKinnon, Lachlan (Labour / Le Travail, 2017)
The article reviews the book, "Smokestacks in the Hills: Rural Industrial Workers in West Virginia," by Lou Martin.